PkM Sosialisasi Aksi Bergizi Sebagai Upaya Pencegahan Anemia pada Siswa di SMPN 3 Garut - Witdiawati Witdiawati; Dadang Purnama; Rohmalia M Noor (GUYUB: Journal of Community Engagement, 2023)
Currently, the prevalence of anemia in adolescents is still high. Anemia in adolescents is one of them caused by insufficient nutritional intake. Socialization is needed to increase adolescent knowledge and understanding of the importance of nutrition to prevent anemia. #AksiBergizi is one of the government's efforts in realizing healthy and anemia-free adolescents. Socialization activities for nutritious actions were carried out at SMPN 3 Garut with a health education method approach through a series of morning exercise activities together, breakfast together, giving material and giving blood-added tablets for female students. The activity was attended by 147 students. Of the total 41 students who were checked for HB, 21 students (51.2%) had low HB. Blood tablets were given to 88 female students.  Socialization of nutritious action is effective in increasing the understanding and knowledge of SMPN 3 Garut students in the prevention of anemia. There needs to be synergy between educational institutions and local health service institutions for the sustainability of school health programs.